Lemmus lemmus ... - Spitsyn, Vitaly M.; Bolotov, Ivan N.; Kondakov, Alexander V.; Klass, Anna L.; Mizin, Ivan A.; Tomilova, Alena A.; Zubrii, Natalia A.; Gofarov, Mikhail Y. (Zenodo, 2021)
Norwegian Lemming Lemmus lemmus (Linnaeus, 1758) Type locality: alpibus Lapponicus [Mountains of Lappmark, Sweden] (Linnaei, 1758). Synonyms: L. norvegicus Desmarest, 1822 [TL: Les montagnes de la Norwege et la Laponie suedoise <...> les montagnes de la Laponie russe] (Desmarest 1822; Wilson & Reeder 2005; Wilson et al. 2017); L. borealis Nilsson, 1829 [a replacement name for Mus lemmus Linnaeus, 1758] (Wilson & Reeder 2005; Wilson et al. 2017); Cuniculus iterator Gistel, 1850 [TL: Russian Lapland =Kola Peninsula, Russia] (Wilson & Reeder 2005; Wilson et al. 2017). Distribution: European mountain species with a disjunctive range: Fennoscandia (nominate subspecies) and Novaya Zemlya (L. lemmus chernovi ssp. nov.). Comments: The insular geographic race on Novaya Zemlya is isolated from the nominate subspecies by a 600 km wide marine barrier (Fig. 1A). ... : Published as part of Spitsyn, Vitaly M., Bolotov, Ivan N., Kondakov, Alexander V., Klass, Anna L., Mizin, Ivan A., Tomilova, Alena A., Zubrii, Natalia A. & Gofarov, Mikhail Y., 2021, A new Norwegian Lemming subspecies from Novaya Zemlya, Arctic Russia, pp. 93-117 in Ecologica Montenegrina 40 on page 115, DOI: 10.37828/em.2021.40.8, http://zenodo.org/record/13233031 ...